Review How Student of Class X SMK Negeri 1 Sungai Rumbai on Student Learning Enggineering Drawings - 1900-1913 , Budi Prasetya (CIVED, 2016)
The research started from a problem student learning is not optimal in training study on the engineering drawings SMK Negeri 1 Sungai Rumbai. Seeing the problem, then do research to describe student learning. With the aim to find out about the picture of student learning in engineering drawings.The type of research is deskriptive. Population this research is graders X TGB at SMK Negeri 1 Sungai Rumbai totaling 25 people. In this study there is only one variable is student learning at engineering drawings. Preparation of research instrument based on the Likert Scale. Before being trials for determine the validity and reliable instrument. The data is statistically analyzed with the help of SPSS versi 20.00.From data analyzed, know that student learning at engineering drawing TGB SMK Negeri 1 Sungai Rumbai in categorized as high and low. Student learning in high category is i take lessons(88%), patterns of student learning (84%), and inspection task(72%). Where as the entry way of learning low category is preparation of student learning (52%) and independent learning activities(60%). Keywods: Student learning, Engineering drawings.